WM-SIMA: Herramienta de simulación para el enlace descendente LTE-Advanced - Delgado-Luque, Isabel-María; Martín-Vega, Francisco-Javier; Carreras, Alberto; Gómez-Paredes, Gerardo; Aguayo-Torres, María del Carmen; Entrambasaguas-Muñoz, José Tomás (My University, 2017)
In this paper, we present a novel and efficient link level simulation framework for the donwlink (DL) of Long Term Evolution Advanced (LTE-A) cellular networks. The tool, called Wireless Mobile SIMulator Advanced (WM-SIMA), is available to be downloaded so that researchers can use it to evaluate the performance for different network conﬁgurations. In this work, the main characteristics of WM-SIMA are presented. As a case of use, the Average Spectral Efﬁciency (ASE) is obtained for the DL of a two-tier network, composed of Macro Access Points (MAPs) and Pico APs (PAPs). Simulation results conﬁrms that there exist an optimal Cell Range Expansion (CRE) bias in the cell association that maximizes the ASE. Interestingly, it is conﬁrmed that this optimal bias does not depend on the number of PAPs, while increasing the number of PAPs leads to a higher ASE for the same bias.
Keywords: Sistemas de comunicaciones móviles; Simulador; LTE; LTE-Advanced; Comunicaciones móviles